Boundedness of Multilinear Calderón-Zygmund Operators on Grand Variable Herz Spaces. (28th March 2022) - Nafis, Hammad; Rafeiro, Humberto; Zaighum, Muhammad Asad
Abstract : In this paper, we prove the boundedness of multilinear Calderón-Zygmund operators on product of grand variable Herz spaces. These results generalize the boundedness of multilinear Calderón-Zygmund operators on product of variable exponent Lebesgue spaces and variable Herz spaces.